The Reliability, Validity, and Student Perceptions of an Undergraduate Research Program in Health Sciences (BHSc) as a Premedical Program: A Preliminary Study (Alberta Journal of Educational Research, 2006)
The purpose of this study was to investigate the reliability and validity of the admission process for an undergraduate research program in health science and to assess the students’ statement of purpose for entering the program. Admission data (high school marks, supplementary application information, and overall rater score) and first-year GPA were analyzed for the 2003-2004 inaugural class (n=55, mean age 17.9 [SD 1.0] years, 61.8% female and 38.2% male). Although the stated purpose of the program is to educate future health researchers, nearly half (43.6%) indicated that their reason for entering the program was to help them to gain admission to medical school. Final high school grades and overall rater scores were the best indicators for first-year performance (multiple R=.66; 42.9% of the variance).